Gen Z: Peduli Terhadap Ekosistem Mangrove di Kelurahan Lalowaru, Konawe selatan - Asriyana Asriyana; La Ode Muhammad Yasir Haya; Sjamsu Alam Lawelle; Haslianti Haslianti; Dedy Oetama (Jurnal Gema Ngabdi, 2023)
Background: The problem of mangrove forest degradation in coastal areas is caused by various factors, including industrial activities, household activities, cultivation activities and land clearing for settlements. Previous research has stated that there needs to be concern from various parties so that mangrove forests in coastal areas are maintained. Until now, mangrove forest destruction, both natural and deliberate, is still quite high, making it a problem in most coastal areas. Situation Analysis: school students as the younger generation play an important role in disseminating knowledge about the importance of maintaining and preserving mangrove forests in coastal areas. Through this activity, it is hoped that a high level of love and concern for the environment can be created for school students in coastal areas. Approach Method: The approach stages carried out in this program consist of educating school students regarding the importance of maintaining mangrove forests in coastal areas. Results and Conclusions: When providing education to school students, they are first given an understanding of the importance of mangrove forests for the environment. After being given education and then practicing planting mangrove seeds directly, school students became enthusiastic about taking part in maintaining the mangrove ecosystem. Based on this, it can be concluded that education for the younger generation regarding the important function of mangrove forests needs to continue to be encouraged so that the younger generation is also involved in preserving coastal areas.